Long-term trajectory of renal dysfunction and related risk factors in patients with apparently treatment-resistant and non-resistant arterial hypertension - Zdeněk Ramík; Jan Václavík; Tomáš Kvapil; Libor Jelínek; Eva Kociánová; Monika Kamasová; Klára Benešová; Jiří Jarkovský; Martin Drápela; Zdeněk Lys (Blood Pressure)
Objectives: Evidence suggests that renal function increasingly deteriorates in patients with apparently treatment-resistant hypertension (ATRH) in comparison with those who have non-resistant arterial hypertension (NAH). We aimed to assess the long-term decline in renal function between these patient groups and identify specific risk factors contributing to the progression of renal dysfunction. Methods: Data for 265 patients with ATRH and NAH in a hypertension excellence centre were retrospectively evaluated. Demographic characteristics, co-morbidities, laboratory findings, secondary causes of hypertension, medication and exposure to contrast agents were assessed. To address differences between groups, adjustment with linear mixed-effect models was used. Results: Data from the first 4 years of follow-up were evaluated. After adjustment for age and diabetes, which were identified as independent risk factors for renal dysfunction progression in the study cohort, the mean decrease in estimated glomerular filtration rate per year was steeper with ATRH than with NAH (−1.49 vs. −0.65 mL/min/1.73 m2 per year; difference in slope, 0.83 mL/min/1.73 m2 per year; 95% confidence interval [CI]: 0.25–1.41, p = 0.005). In subgroup analyses, without Holm–Bonferroni correction, the prescription of MRA indicated a faster decline in renal function in ATRH. Following correction, no specific therapeutic risk factor was associated with faster progression of renal dysfunction. Conclusions: Renal function declines twice as fast with ATRH compared with NAH, independently of age and diabetes. Larger studies are needed to reveal risk factors for renal dysfunction in patients with hypertension.